2021
DOI: 10.3389/fgene.2021.666396
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Based Estrogen Related Genes Biomarkers for Diagnosis and Prognosis in Non-small Cell Lung Cancer

Abstract: BackgroundLung cancer is the tumor with the highest morbidity and mortality, and has become a global public health problem. The incidence of lung cancer in men has declined in some countries and regions, while the incidence of lung cancer in women has been slowly increasing. Therefore, the aim is to explore whether estrogen-related genes are associated with the incidence and prognosis of lung cancer.MethodsWe obtained all estrogen receptor genes and estrogen signaling pathway genes in The Cancer Genome Atlas (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…Downregulation of FKBP3 suppressed breast cancer [ 81 ], and FKBP3 expression was associated with poor survival in LUAD [ 82 , 83 , 84 ]. Furthermore, FKBP4 was reported to be related to breast cancer [ 20 , 85 ], colorectal cancer [ 22 ], prostate cancer [ 86 ], and lung cancer [ 21 , 87 ]. FKBP10 was connected with gastric cancer [ 88 ], stomach adenocarcinomas [ 89 ], papillary thyroid cancer [ 90 ], and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of FKBP3 suppressed breast cancer [ 81 ], and FKBP3 expression was associated with poor survival in LUAD [ 82 , 83 , 84 ]. Furthermore, FKBP4 was reported to be related to breast cancer [ 20 , 85 ], colorectal cancer [ 22 ], prostate cancer [ 86 ], and lung cancer [ 21 , 87 ]. FKBP10 was connected with gastric cancer [ 88 ], stomach adenocarcinomas [ 89 ], papillary thyroid cancer [ 90 ], and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LSCC is a common type of malignant tumour with a high burden of mortality, causing approximately 400,000 deaths worldwide every year 1 . In recent years, numerous studies have been conducted to explore the diagnosis, progression, prognosis and treatment of LSCC 31 , 32 . Some traditional tumor markers have been applied in screening, occurrence and prognosis prediction for LSCC 33 , including squamous cell carcinoma antigen (SCC), carcino-embryonic antigen (CEA), cytokeratins21-2 and neuron specific enolase (NSE).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, specific studies were carried out to discover the correlation between the ADCY9 gene and LUAD. It was reported that ADCY9 might be associated with the estrogen signaling pathway in LUAD, which may improve the prognosis of LUAD patients ( 46 ). Further, research exhibited that the Phospholipase C Signaling network, including mutated genes like ADCY9 , ADCY2 , and GNB5 , may indicate the facilitation of lung metastasis from colon cancer ( 47 ).…”
Section: Discussionmentioning
confidence: 99%